Kontribusi Partai Politik Terhadap Pembangunan Demokrasi Dalam Perspektif Hukum Tata Negara - Yunita Nurul Arifah; Dwi Maulida Khasanah; Can Gita Yuliana; Aqilla Fayyaza Ghafur; Niken Fernanda; Rosa Adelia Arifin; Kuswan Hadji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Political parties play a vital role in advocating for democracy and maintaining public trust in the political system. This study evaluates the role of political parties in the development of democracy from the perspective of constitutional law using a qualitative descriptive method. They are responsible for transparency, participation, and accountability in the political process, as well as formulating policies, raising political awareness, and representing the interests of the people. Political parties also support political pluralism, participate in elections, and oversee the government in accordance with the law. Despite their key role in building democracy, challenges such as unequal representation and lack of transparency still need to be addressed. This research provides insights into the contribution of political parties to strengthening democracy, while highlighting areas that require further attention to improve the quality of democracy in Indonesia.